The Impact of Adoption and Utilization Of E-Learning Technology by Employees on the E-Learning System on Organizational Learning: Mediating Role of Service Quality of the E-Learning System - MASOOD, KHANSA; JABEEN, SADIA; TARIQ, SAMRA; RUBBANI, FOUZIA MARYAM (The journal of contemporary issues in business and government, 2021)
The study is carried out on the issues related to adoption and utilization of e-learning technology by employees, e-learning system on organizational learning, and service quality of the e-learning system. The study has examined the direct impact of adoption and utilization of e-learning technology by employees on the e-learning system on organizational learning. Meanwhile, the study has also examined the mediating role of service quality of the e-learning system. A 5-point Likert scale was adopted for the survey questionnaire for all the items. Number 1 on the scale referred to strongly disagree, and number 5 referred to strongly agree. The response rate of the study is 58 percent. The data is collected from the undergraduate student at Pakistani public public universities. The time frame of the study is between June 2020 to January 2021. The SEM-PLS is employed for the data analysis , which is one of the robust statistical tool for examining the structural models. It has been revealed by this research that organizational learning is directly influenced by employee satisfaction for the adoption and use of e-learning technology. However, the service quality of e-learning does not have a direct influence on institutional learning. The relationship between organizational learning effectiveness and service quality of the e-learning system has been fully mediated by the employee satisfaction of using e-learning technology.